For the Earth That Has Never Been - Marder, Michael (Stasis, 2020)
In this article, I advance four main theses:1) that there has never been a philosophy of the earth; 2) that the earth has never been itself;3) that the earth has never been defined; and4) that the earth has never been moral.I suggest that a geophilosophy worthy of the name would need to respect these negative qualities of the earth’s non-identity, non- or indefiniteness, and a-morality.